The Effect of Less-Lethal Weapons on Injuries in Police Use-of-Force Events - MacDonald, John M. (American Public Health Association, 2009)
Objectives. We investigated the effect of the use of less-lethal weapons, conductive energy devices (CEDs), and oleoresin capsicum (OC) spray on the prevalence and incidence of injuries to police officers and civilians in encounters involving the use of force. Methods. We analyzed data from 12 police departments that documented injuries to officers and civilians in 24 380 cases. We examined monthly injury rates for 2 police departments before and after their adoption of CEDs. Results. Odds of injury to civilians and officers were significantly lower when police used CED weapons, after control for differences in case attributes and departmental policies restricting use of these weapons. Monthly incidence of injury in 2 police departments declined significantly, by 25% to 62%, after adoption of CED devices. Conclusions. Injuries sustained during police use-of-force events affect thousands of police officers and civilians in the United States each year. Incidence of these injuries can be reduced dramatically when law enforcement agencies responsibly employ less-lethal weapons in lieu of physical force.